PERAN NEGARA DALAM PENGELOLAAN SUMBER DAYA KELAUTAN BERBASIS KEARIFAN LOKAL UNTUK KESEJAHTERAAN YANG BERKEADILAN - Safaat, Rachmad; Yono, Dwi (Faculty of Law, University of Muhammadiyah Malang, 2017)
Marine and coastal area management is necessary to be operated comprehensively and sustainable. The existence of indigenous peoples and traditional society has a role in the marine and coastal areas management, but the legislation has not been fully giving more protection in its management. Economic base development, generally often ignore local society wisdom, so that a clean environment is being polluted as a result of that waiver. Development that materialistic value oriented, only the physical build that actually provide benefits to investors and not the community itself. What kind of justice that ideally obtained by indigenous and traditional peoples to achieve justice that bring prosperity? The government has neglected and must fix the policies in the legislation as a foundation for development without neglecting the indigenous people themselves. Equitable development not just physically, but sustainable development to preserve nature by observing local society wisdom that have taken place to the next. The government still considered neglectful for environmental management.